GASTROINTESTINAL COMPLICATIONS OF PATIENTS WITH DIABETES MELLITUS: ISSUES OF DIAGNOSIS AND TREATMENT - Abdusattarov A.A (Western European Studies, 2024)
Diabetes mellitus (DM) is a disease characterized by multiple organ lesions, the formation of complications such as diabetic neuropathy, retinopathy, nephropathy, etc. About 75% of patients with DM report the presence of clinically significant gastrointestinal symptoms during examination and treatment. The food canal in DM is affected throughout, starting from the oral cavity and esophagus and ending with the large intestine and anorectal area. At the same time, clinical manifestations are often mosaic in nature and can vary significantly. The classic gastrointestinal symptoms in DM are abdominal pain, bloating, nausea, a feeling of rapid satiety, postprandial discomfort, diarrhea and/or constipation, and the frequency of symptoms characteristic of gastroesophageal reflux disease (heartburn, dysphagia) reaches 41% of cases
Keywords: confidence interval; gastrointestinal tract; coronary heart disease